Participatory Budgeting In Indonesia Private University - Sayidah, Nur; Assagaf, Aminullah (AKRUAL: JURNAL AKUNTANSI, 2018)
This study aims to explore participatory budgeting practices of a private university in Surabaya. The research method use qualitative approach. The research site is Dr. Soetomo Surabaya. Informants in this study were Rector, Vice Retor, Deans and Head of Internal Audit. The data collection is mainly with participating observation. Researchers as vice chairman of the budget committee could follow budgeting process began with budget committee meetings, leaders meetings, senate meeting until the meeting with the foundation. Data were analyzed with Miles and Huberman's (1992) qualitative analysis technique. The result indicates that Vice Rector II acts as a leader have in the context of budgeting. Rector as a leader in university level and Chairman of the Foundation acts as a leader at the foundation level. Harmony and togetherness in the budgeting process is reflected in the participation of some players in establishment of work program. This process is in a way democratic. While, the balance is reflected in the process of budgetary increase in allowances.